2021
DOI: 10.1530/eje-20-1490
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of patients and clinicians for treatment of Graves’ disease: a discrete choice experiment

Abstract: Objective: Treatment options for Graves’ disease (GD) consist of antithyroid drugs (ATD), radioactive iodine (RAI) and total thyroidectomy (TT). Guidelines recommend to discuss these options with patients, taking into account patients’ preferences. This study aims to evaluate and compare patients’ and clinicians’ preferences and the trade-offs made in choosing treatment. Design and methods: A discrete choice experiment (DCE) was performed with GD patients with a first diagnosis or recurrence in the previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In practice, around half of patients treated with 12 to 18 months of ATD therapy will achieve remission, with remission defined as euthyroidism 3 to 6 months after the last administered dose of ATD. Most of these patients will remain euthyroid once normal thyroid indices are achieved ( 9 , 10 ). Current guidelines suggest that treatment approach in hyperthyroidism should be individualized and part of a shared decision-making process with each patient.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, around half of patients treated with 12 to 18 months of ATD therapy will achieve remission, with remission defined as euthyroidism 3 to 6 months after the last administered dose of ATD. Most of these patients will remain euthyroid once normal thyroid indices are achieved ( 9 , 10 ). Current guidelines suggest that treatment approach in hyperthyroidism should be individualized and part of a shared decision-making process with each patient.…”
Section: Discussionmentioning
confidence: 99%
“…21 , 22 , 23 These techniques have previously been used in otolaryngology and thyroid surgery. 17 , 24 , 25 , 26 , 27 , 28 Studies have demonstrated that antithyroid drugs for Graves disease were generally preferred by patients over surgery or radioactive iodine, 29 that significant cosmetic considerations regarding thyroid surgery should be factored into decision‐making, 30 and that risk of needing a subsequent contralateral hemithyroidectomy for those undergoing unilateral procedures is a significant driver of decision‐making. 31 (Although the topic of hemithyroidectomy was not explicitly addressed in our study, the underlying concerns regarding total vs hemithyroidectomy were explored through discussion of the need for lifelong medication and the risk of potential recurrence.)…”
Section: Discussionmentioning
confidence: 99%
“…In a recent, multicenter study conducted in the Netherlands, van Kinschot et al 41 performed a discrete choice experiment regarding the three management options for primary and first relapse GD presentation. The study included 286 patients and 61 clinicians.…”
Section: Referral For Surgery In the Treatment Of Gdmentioning
confidence: 99%